Pengaruh Beban Kerja terhadap Turnover Intention Melalui Kepuasan Kerja sebagai Intervening pada Karyawan PT Central Motor Wheel Indonesia - Retmawanto, Irfanadi; Suherman, Enjang; Hidayaty, Dwi Epty (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Various types of industrial sectors, both service industries and manufacturing industries, are still often faced with turnover problems. To prevent the turnover rate from increasing, the company must be able to observe the factors driving employees to decide to leave the company. The factors driving turnover intention can consist of various things, including workload and job satisfaction. This research aims to determine the effect of workload on turnover intention through job satisfaction as an intervention for employees of PT Central Motor Wheel Indonesia. This research uses a quantitative data analysis method which is used to examine the magnitude of the direct and indirect contribution of the influence of workload on turnover intention through job satisfaction as an intervening factor. The data analysis technique uses descriptive analysis and Path Analysis path analysis with the help of SPSS version 25. The variables observed in this research consist of workload as an independent variable, turnover intention as the dependent variable and job satisfaction as an intervening variable. The population of this research was 178 employees of PT Central Motor Wheel Indonesia and the sample of this research was 123 employees. The research results show that workload has a negative and significant effect on job satisfaction, the effect of job satisfaction on turnover intention has a negative and significant effect, the effect of workload and turnover intention is negative and significant. From the Sobel test calculations, the values obtained prove that the influence of workload on turnover intention through job satisfaction as an intervening has a significant effect.